International communities of invention and innovation : IFIP WG 9.7 International Conference on the History of Computing, HC 2016, Brooklyn, NY, USA, May 25-29, 2016, revised selected papers /: IFIP WG 9.7 International Conference on the History of Computing, HC 2016, Brooklyn, NY, USA, May 25-29, 2016, revised selected papers. (2016) - Unknown
No abstract available